Pengajaran Lingkungan Rumah Berdasarkan Kepedulian pada Kehidupan Murid SD Sehari-hari - Laurens Kaluge (Universitas Negeri Malang, 2016)
This study examined the Sidoarjo School Improvement Program (SSIP), after a year in action, emphasizing the teaching improvement based on the current concepts of effective teaching. The Social Studies particularly on home environment was the case of application. There were 19 primary schools involved as the experimental and 15 as the control schools, involving 781 Grade 3 pupils representing the urban, semi-urban, and rural subdistricts. The data were collected by using intelligence test, content-related test, questionnaire for pupils and parents, inventories, and open questionnaires. After controlling for the childs ability (intelligence), gender, parental occupation and education, family supports, self-concept, democratic atmosphere, and locus of control; no difference was found among urban, semi-urban, and rural schools. However, the most striking result was that the SSIP made a difference, the attainments of children at experimental schools were higher than those at the control schools.